Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose Preclinical studies suggest that poly(ADP-ribose) polymerase (PARP) inhibition enhances tumor immunogenicity through STING pathway activation, providing rationale for combination with immune checkpoint inhibitors. However, clinical evidence supporting this synergy remains limited. We conducted a neoadjuvant pilot study evaluating olaparib with or without pembrolizumab in homologous recombination deficiency (HRD)-positive advanced ovarian cancer. Patients and methods Patients with newly diagnosed, HRD-positive FIGO stage III-IV high-grade serous or endometrioid ovarian cancer were enrolled. HRD status was determined using the Myriad MyChoice HRD Plus test. Patients received olaparib monotherapy (300 mg twice daily for 6 weeks; Cohort 1, n=10) or olaparib plus pembrolizumab (200 mg every 3 weeks for two cycles; Cohort 2, n=20), followed by surgery and platinum-based chemotherapy. The primary endpoint was overall response rate (ORR). Exploratory immunohistochemical and single-cell RNA sequencing analyses assessed tumor microenvironmental changes. Results ORR was 50.0% (95% CI, 18.7-81.3) in Cohort 1 and 70.0% (95% CI, 45.7-88.1) in Cohort 2 (p=0.2839). In Cohort 1, responses occurred only in BRCA2-mutated tumors (5/5, 100%). In Cohort 2, ORR was 84.6% (11/13) in BRCA1/2-mutated tumors and 42.9% (3/7) in non-BRCA1/2-mutated tumors. PD-L1 expression, tumor mutational burden, and microsatellite instability were not associated with response. Olaparib monotherapy did not increase tumor immunogenicity, while the combination increased CD8+ T-cell infiltration and immune-related transcriptional changes. No unexpected toxicities were observed. Conclusions Neoadjuvant olaparib showed measurable radiographic activity in HRD-positive advanced ovarian cancer. Pembrolizumab enhanced immune activation, but its impact on early clinical response appeared limited.